An incentive-aware blockchain-based solution for internet of fake media things. Issue 6 (November 2020) - Chen, Qian; Srivastava, Gautam; Parizi, Reza M.; Aloqaily, Moayad; Ridhawi, Ismaeel Al
Highlights: The impact of Fake News is unprecedented due to technology that can proliferate the news globally as fast as a viral spread. Innovative ways to produce and spread false content including text, images, and videos with the intent of deceiving its audience has also expanded. This paper proposes a prevention system to Fake News rather than only a detection system through a customized Blockchain Proof-of-Authority protocol. An applicable scenario of Blockchain technology outside of its financial roots has been implemented as well. Abstract: The concept of Fake Media or Internet of Fake Media Things (IoFMT) has emerged in different domains of digital society such as politics, news, and social media. Due to the integrity of the media being compromised quite frequently, revolutionary changes must be taken to avoid further and more widespread IoFMT. With today's advancements in Artificial Intelligence (AI) and Deep Learning (DL), such compromises may be profoundly limited. Providing proof of authenticity to outline the authorship and integrity for digital content has been a pressing need. Blockchain, a promising new decentralized secure platform, has been advocated to help combat the authenticity aspect of fake media in a context where resistance to the modification of data is important. Although some methods around blockchain have been proposed to take on authentication problems, most current studies are built on unrealistic assumptions with the after-the-incident type of mechanisms. In this article, we propose a preventative approach using a novel blockchain-based solution suited for IoFMT incorporated with a gamification component. More specifically, the proposed approach uses concepts of a customized Proof-of-Authority consensus algorithm, along with a weighted-ranking algorithm, serving as an incentive mechanism in the gamification component to determine the integrity of fake news. Although our approach focuses on fake news, the framework could be very well extended for other types of digital content as well. A proof of concept implementation is developed to outline the advantage of the proposed solution.